Globalne uwarunkowania wzrostu konkurencyjności Unii Europejskiej w XXI wieku - Puślecki, Zdzisław W. (Przegląd Politologiczny, 2018)
The paper aims to present the global determinants of the increased competitiveness of the European Union in the 21st century. Its detailed purpose was to determine the position of the European Union vis-à-vis the USA and Japan, to indicate the role of innovation and employment in the increased competitiveness of the EU, the position of the Common Agricultural Policy under the circumstances of increased competition, the increased importance of ser- vices, the position of the European Union as compared to the competitiveness of BRIC, and how the EU functions within WTO principles. The analysis of these research issues indicates that the European Union is facing a number of significant challenges in the early 21st century. Those related to the prices of goods and resources are particularly worth pointing out. They are closely, mutually related and concern political issues in the field of financial markets, de- velopment, trade, industry and external relations.